The relationship of teacher certification, work motivation, and the working period with the performance of physical education teachers of elementary schools - Pratama, Christianus Yanuarli Agung; Sukarmin, Yustinus (Journal of Education, Health and Sport, 2019)
Aim: This study aims to determine the relationship between teacher certification, work motivation, and working period with the performance of elementary school physical education teachers individually and simultanuously in the Yogyakarta West Region UPT.Methods: This research is a quantitative correlational research. The population in this study were all teachers of state and private elementary schools in the Western Yogyakarta UPT with a total of 26 teachers. Data collection was carried out using documentation, observations and questionnaires that had been tested for their validity and reliability. The data analysis technique used was product moment correlation with a significance level of 5% which was tested using the help of SPSS version 22.0.Result: The results showed that: (1) there was a relationship between teacher certification and the performance of elementary school physical education teachers in the Yogyakarta West Region UPT, as proven by the r count of 0.496; significance value 0.010 <0.05; and the amount of relationship was 24.6%; (2) there was a relationship between work motivation and the performance of elementary school physical education teachers in the Yogyakarta West Region UPT, as indicated by the r count of 0.621; significance value of 0.001 <0.05; and the amount of relationship was 38.5%; (3) there was a relationship between the working period and the performance of elementary school physical education teachers in the Yogyakarta West Region UPT, as indicated by the r count of 0.481; significance value of 0.013 <0.05; and the amount of relationship was 23.2%; and (4) there was simultanuous a relationship between teacher certification, work motivation, and work period with the performance of elementary school physical education teachers in the Western Region Yogyakarta UPT, as proven by an F count of 12,511; significance value of 0.000 <0.05; and the amount of relationship was 63.0%.Conclusion: The result of the research is 1) There is a correlation between teacher certification and the performance of the Physical Education teachers of Primary School in the UPT Yogyakarta in the Western Region. 2) There is a correlation between work motivation and the performance of Physical Education teachers of a primary school in the UPT Yogyakarta in the Western Region. 3) There is a correlation between the work period and the work of the Physical Education teachers of the primary school in the UPT Yogyakarta in the Western Region. 4) There is a correlation together with teacher certification, work motivation, and working period with the staff of Physical Education teachers of a primary school in the UPT Yogyakarta in the Western Region.